DIALECTOLOGY: FROM GILLIÉRON TO NOWADAYS (Muitas Vozes, 2021)
Due to the human’s interest for the language, and after that for its variation, this paper aims to deepen the discussion about linguistic variation according to three areas of linguistics studies: Sociolinguistics (LABOV, 2008 [1972]); Dialectology (COSERIU, 1957; FERREIRA, 1994; CARDOSO, 2010); and Pluridimensional Dialectology (THUN, 1998). Therefore, we resort to a historical review of the theorical references from each area. Thereby, we manage to notice the studies about linguistic variation importance, and how Dialectology, for instance, has incorporated Sociolinguistics analysis method, and vice-versa. Lastly, we concluded that dialectological studies and sociolinguistic studies are imbricated and constantly developing.